2020
DOI: 10.1007/s12035-020-02085-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Synuclein-Transgenic Mouse Model for Early Parkinson’s Reveals Molecular Features of Preclinical Disease

Abstract: Understanding Parkinson’s disease (PD), in particular in its earliest phases, is important for diagnosis and treatment. However, human brain samples are collected post-mortem, reflecting mainly end-stage disease. Because brain samples of mouse models can be collected at any stage of the disease process, they are useful in investigating PD progression. Here, we compare ventral midbrain transcriptomics profiles from α-synuclein transgenic mice with a progressive, early PD-like striatal neurodegeneration across d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 137 publications
(177 reference statements)
0
3
0
Order By: Relevance
“… 47 , 48 Our results are in line with previous studies that identified OMD as a potential blood biomarker for PD 49 and upregulated in a SNCA transgenic mouse model. 50 A recent study has also shown the elevated expression of CD44 in the substantia nigra of human PD brains and CD44-mediated anti-inflammatory effects in primary mouse astrocytes. 51 Induced expression of CD44 by α-synuclein in microglia, likely affecting PD pathogenesis by recruiting reactive microglia into the pathological region of the PD brain, was also reported.…”
Section: Discussionmentioning
confidence: 96%
“… 47 , 48 Our results are in line with previous studies that identified OMD as a potential blood biomarker for PD 49 and upregulated in a SNCA transgenic mouse model. 50 A recent study has also shown the elevated expression of CD44 in the substantia nigra of human PD brains and CD44-mediated anti-inflammatory effects in primary mouse astrocytes. 51 Induced expression of CD44 by α-synuclein in microglia, likely affecting PD pathogenesis by recruiting reactive microglia into the pathological region of the PD brain, was also reported.…”
Section: Discussionmentioning
confidence: 96%
“…Disruption of the dopaminergic system is implicated in neurological diseases such as Parkinson’s disease (PD) and Huntington’s disease. PD involves the progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNc), leading to motor deficits and potentially non-motor disorders like mild cognitive impairment (MCI) and dementia ( Kikuchi et al, 2017 ; Hendrickx et al, 2021 ). 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a useful tool to induce the development of both late and early PD models, can reproduce both motor and non-motor symptoms ( Grandi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the chronic effects leading to the apoptotic death of dopaminergic neurons in the substantia nigra pars compacta (SNc), these substances can also be used to explore more subtle effects on dopaminergic axons or varicosities. Neuropathological and neurological changes might occur before obvious neurodegeneration, potentially triggered by environmental toxins or genetic factors ( Grandi et al, 2018 ; Hendrickx et al, 2021 ). Therefore, investigating alterations in dopamine release probabilities caused by low concentrations of the neurotoxin MPP + and exploring protective approaches is an important research objective ( Lisman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%